Sexting: a comparative study of child sexual criminalogy between Australia and Malaysia / Nur Liyana Rosli, Nur Shafiqah Nor Azelan and Fatimah Zubaidah Mohd Zabidi - Rosli, Nur Liyana; Nor Azelan, Nur Shafiqah; Mohd Zabidi, Fatimah Zubaidah (2010)
There are quite a similarity between laws in Malaysia and Australia. However, in Australia the laws regarding sexting are clearer and such offence has its own specific provisions which make it a crime upon practicing it as ccriminal law affects sexting in several ways. Out of the areas of criminal law that affect sexting, child pornography has, by far, gained the most attention in the media and academic debate. The reason is obvious - child pornography laws, put in place to protect children from one of the world's most universally condemned criminal activities, are being used to charge teenagers who voluntarily capture and communicate images or videos of themselves. For the teenager who commits sexting, they are at risk of being prosecuted under child pornography charges because of discrepancies in state and federal laws. This is because the for example, the age of consent in NSW is 16 - and the legal definition of a child in NSW is the same - under the Commonwealth Criminal Code, a child is defined as anyone under the age of 18. If a child is charged with a crime like this, he or she could be placed on the child-sex register which could in turn, could affect his or her employment and travel prospects. Hence to avoid such consequences which will ruin the child later on, the authority should take account of sexting as a common practice among young people, in order to avoid criminalizing or stigmatizing young people as child sex offenders. The key task in relation to the ways would be to find some sort of exception, defense or something along those lines excluding sexting from child pornography offences while at the same time avoiding creating some sort of a loophole that can be used by serious child pornography offenders.